2016
DOI: 10.1016/j.celrep.2016.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Confinement Sensing and Signal Optimization via Piezo1/PKA and Myosin II Pathways

Abstract: SUMMARYCells adopt distinct signaling pathways to optimize cell locomotion in different physical microenvironments. However, the underlying mechanism that enables cells to sense and respond to physical confinement is unknown. Using microfabricated devices and substrate-printing methods along with FRET-based biosensors, we report that, as cells transition from unconfined to confined spaces, intracellular Ca2+ level is increased, leading to phosphodiesterase 1 (PDE1)-dependent suppression of PKA activity. This C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
136
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(146 citation statements)
references
References 57 publications
4
136
0
Order By: Relevance
“…Physical cues, such as confinement, strongly influence tumour cell trafficking 19,46,47 . As confinement increases, it becomes more challenging for a cell to deform sufficiently so that it can squeeze into narrow spaces.…”
Section: Physical Limits On Cell Motilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Physical cues, such as confinement, strongly influence tumour cell trafficking 19,46,47 . As confinement increases, it becomes more challenging for a cell to deform sufficiently so that it can squeeze into narrow spaces.…”
Section: Physical Limits On Cell Motilitymentioning
confidence: 99%
“…When the cross-sectional area of interfibrillar pores is less than ~7 μm 2 , matrix degradation is required for cancer cell migration to occur 18 , as discussed in detail below. Evidence suggests that confinement is a physical cue that modulates intracellular signalling 19 , thereby altering tumour cell migration mechanisms. This Opinion article discusses confined cancer cell motility, focusing on its in vivo relevance, migration mechanisms and confinement-induced cell responses.…”
mentioning
confidence: 99%
“…These include cell indentation [2], membrane stretch [2], shear flow [23,24], substrate stiffness [25], substrate nanotopology [26], tissue compression [27], tissue distention [28], confinement [29], and osmotic stress [30]. The diverse nature of the activating stimuli naturally raises the question: what are the relevant physical and cellular parameters that gate the channel?…”
Section: Effects Of the Cytoskeleton On Piezo1 Activationmentioning
confidence: 99%
“…Hung et al found that Piezo1 is also involved in confined migration [29]. Cells are induced to migrate in confined spaces through bioengineered fibronectin-coated microchannels or along 8 um- wide 1D fibronectin-printed lines.…”
Section: Effect Of Piezo1 Activity On the Cytoskeletonmentioning
confidence: 99%
See 1 more Smart Citation